A liquid breakdown driven non-invasive microjet injection system. (June 2021) - Ham, Hwichan; Yoh, Jack J.
Highlights: l Liquid breakdown can produce microjet stream reaching 330 m/s at 40 µs pulse. l Microjet reaches the targeted skin layer with minimum tissue destruction. l Dielectric breakdown has 21 times higher energy efficiency over the laser source. l Medical effectiveness was tested via in vivo procedure on the diabetic mouse model. Abstract: The purpose of this study was to develop a microjet having fully skin-penetrable jet speed, moderately small volume, and highly repeatable injection, and eventually providing a device with medical efficacy for less tissue destruction and pain. The injector allows a small volume of drug stream (0.1–1.7 µL) to flow out at a frequency of ~16 Hz, and employs two different sources of energy, namely electrical and optical, which are converted into kinetic energy of the penetrating drug solution using liquid breakdown (dielectric or laser-induced). The medical efficacy of the microjet injection was evaluated through ex-vivo and in-vivo procedures in a mouse model. Both sources of liquid breakdown generate a skin-penetrable jet speed of 200–330 m/s. These fast and repetitive jets in a small volume pass through the epidermis to exert their efficacy. The driving pressure provided by dielectric breakdown showed an extensive increase per input energy increase, which is deemed appropriate for deep skin penetration. In contrast, the laser-induced breakdown exhibited a saturation in jet speed with increasing input energy, which is indicative of a low energy conversion efficiency. The results are promising for medical procedures that require uniform drug injection over a large area, and small dosage control during intradermal procedures.